2012
DOI: 10.1242/dev.070276
|View full text |Cite
|
Sign up to set email alerts
|

FGF/MAPK signaling is required in the gastrula epiblast for avian neural crest induction

Abstract: SUMMARYNeural crest induction involves the combinatorial inputs of the FGF, BMP and Wnt signaling pathways. Recently, a two-step model has emerged where BMP attenuation and Wnt activation induces the neural crest during gastrulation, whereas activation of both pathways maintains the population during neurulation. FGF is proposed to act indirectly during the inductive phase by activating Wnt ligand expression in the mesoderm. Here, we use the chick model to investigate the role of FGF signaling in the amniote n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 71 publications
(111 reference statements)
8
91
1
Order By: Relevance
“…Examination of NC markers at differentiation day 5 revealed decreased expression of all examined NC genes when PD 173074 was administered continuously for 5 days (Fig. 7B), suggesting that FGF signaling is required for human NC induction in accordance with previous findings from animal models (Stuhlmiller and Garcia-Castro, 2012b). WNT signaling is known to promote mesoderm induction in differentiating hESCs (Funa et al, 2015;Sumi et al, 2008).…”
Section: Human Neural Crest Induction Requires An Early and Balanced supporting
confidence: 88%
See 1 more Smart Citation
“…Examination of NC markers at differentiation day 5 revealed decreased expression of all examined NC genes when PD 173074 was administered continuously for 5 days (Fig. 7B), suggesting that FGF signaling is required for human NC induction in accordance with previous findings from animal models (Stuhlmiller and Garcia-Castro, 2012b). WNT signaling is known to promote mesoderm induction in differentiating hESCs (Funa et al, 2015;Sumi et al, 2008).…”
Section: Human Neural Crest Induction Requires An Early and Balanced supporting
confidence: 88%
“…Endogenous FGF signaling is required for NC induction, and exogenous FGF triggers mesoderm character FGF signaling has been implicated in NC induction in animal models, either acting directly on NC precursors or via mesoderm induction (Mayor et al, 1997;Stuhlmiller and Garcia-Castro, 2012b;Yardley and Garcia-Castro, 2012). Treatment of differentiating hESCs with PD 173074, an FGFR1-and FGFR3-specific inhibitor, repressed the expression of the FGF targets SPRY1 and SPRY2 by 40-50% (Fig.…”
Section: Human Neural Crest Induction Requires An Early and Balanced mentioning
confidence: 98%
“…FGFs have been shown to sensitize the dorsal ectoderm to respond to BMP inhibition, transcriptionally regulate BMPs and Wnts, and to contribute directly to NPB specification. 19,20,[54][55][56] In Xenopus, the DLMZ expresses a number of paracrine growth factors at the onset of gastrulation including wnt8, fgf4, fgf8, gdf6 and the BMP antagonist chordin (Fig. 2) and further expresses hairy2, fgfr1, fgfr4a, bmpr1a, pcns and ror2.…”
Section: Sources Of Wnt and Fgf Ligandsmentioning
confidence: 99%
“…We recently have shown that FGF signaling can modulate Pax7 in the early chick ectoderm (Stuhlmiller and García-Castro, 2012a;Yardley and García-Castro, 2012). Among putative effectors of FGF/ERK signaling are the ETS TFs.…”
Section: Discussionmentioning
confidence: 99%
“…This restricted expression offers a unique opportunity to advance our understanding of early events of NC formation. The expression of Pax7 has been analyzed in different contexts in various organisms, and it is known to be responsive to BMP, Wnt and FGF signals (Liem et al, 1997;Liem et al, 2000;Litingtung and Chiang, 2000;Briscoe et al, 2001;Basch et al, 2006;Otto et al, 2006;Maczkowiak et al, 2010;Stuhlmiller and García-Castro, 2012a). Analysis of mouse genomic sequences upstream of Pax7 identified a 10 kb region able to recapitulate endogenous Pax7 expression in only a few migratory cranial NC cells and the roof plate (Lang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%